2012
DOI: 10.1002/rem.21333
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of MicroBlower™ technology for sustainable soil vapor extraction: Case studies at the Savannah River Site, South Carolina

Abstract: The MicroBlower Sustainable Soil Vapor Extraction System is a cost-effective device specifically designed for remediation of organic compounds in the vadose zone. The system is applicable for remediating sites with low levels of contamination and for transitioning sites from active source technologies such as active soil vapor extraction to natural attenuation. It can also be a better choice for remediating small source zones that are often found in "tight zones" that are controlled by diffusion rate. The Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…These observations were reported for vapor extraction wells associated with the former 782-5M SVEU that was located just north of the MASB along the abandoned process sewer line. In contrast, it was recently reported that 24-volt Microblowers have a radius of influence of 41 feet when operating at 10.3 scfm (Noonkester et al, 2012a). The later investigation was performed between the 782-5M SVEU and the WSTS location.…”
Section: Estimate Of Well Performance Using Microblower™ Technologymentioning
confidence: 95%
See 3 more Smart Citations
“…These observations were reported for vapor extraction wells associated with the former 782-5M SVEU that was located just north of the MASB along the abandoned process sewer line. In contrast, it was recently reported that 24-volt Microblowers have a radius of influence of 41 feet when operating at 10.3 scfm (Noonkester et al, 2012a). The later investigation was performed between the 782-5M SVEU and the WSTS location.…”
Section: Estimate Of Well Performance Using Microblower™ Technologymentioning
confidence: 95%
“…The majority of these wells are located in Parcel 2 with VEW-15A located in Parcel 3, VEW-23F located in Parcel 4, and VEW-34F located in Parcel 1. In comparison to other MicroBlower™ deployments (Noonkester et al, 2012a) these wells have larger diameters (4 and 6-in) and have screen lengths ranging from 30 to 120 feet. These parameters couple to create large well bore volumes that facilitate the use of the highest capacity systems available.…”
Section: Estimate Of Well Performance Using Microblower™ Technologymentioning
confidence: 97%
See 2 more Smart Citations
“…Wells that are identified as candidates for transition to low energy operation are further analyzed and estimates of performance under MicroBlower™ extraction are performed. This utilizes earlier observations on the performance of these systems within A/M Area (Noonkester et al, 2012a).…”
Section: Estimate Well Performance Using Microblower™ Technologymentioning
confidence: 99%